أثر برنامج مقترح بالتدريب البليومتري لتطوير القوة الانفجارية والارتقاء والتسديد لدى لاعبي كرة القدم أقل من19 سنة - بومعزة صلاح الدين (My University, 2023)
............................................................Abstract............................................................... The study aimed to investigate the impact of a proposed plyometric training program on the development of explosive power, jumping ability, and shooting distance using plyometric exercises on selected physical abilities of U19 soccer players. The experimental method was employed as the most suitable approach for this study. The sample consisted of 22 players from the Sederata Union Club, which competes at the regional level in Annaba. The sample was purposefully selected, and pre-tests were conducted for both the control and experimental groups. Explosive power, jumping ability, and shooting distance were measured, and a set of plyometric exercises specific to soccer was designed to enhance explosive power, jumping ability, and shooting distance. After implementing the program, post-tests were carried out, and the following conclusions were reached: • Plyometric training had a significant impact on developing explosive power in U19 soccer players. • Plyometric training had a significant impact on improving jumping ability in U19 soccer players. • Plyometric training had a significant impact on enhancing shooting ability for longer distances in U19 soccer players. Based on the study's findings, the researcher proposed the following suggestions: • Emphasizing the use of plyometric training to develop physical capabilities. • Ensuring the inclusion of plyometric programs in coaches' annual plans. • Encouraging those involved in soccer to design and distribute well-structured plyometric training curricula for maximum benefit. ..................................................................ملخص الدراسة......................................................... ملخص الدراسة: هدفت الدراسة إلى التعرف على أثر برنامج تدريي مقترح بليومتري في تطوير القوة الانفجارية و التسديد و الارتقاء باستخدام تدريبات البليومتري على بعض القدرات البدنية لدى لاعبي كرة القدمU19 ، وقد إستخدمنا المنهج التجريبي الذي يعد الأنسب لهذه الدراسة، ولتحقيق ذلك تكونت العينة من 22 لاعبا من نادي إتحاد سدراتة الذي ينشط على مستوى الجهوي الأول عنابة وكانت العينة قصدية وقمنا بالاختبارات القبلية للمجموعتين الضابطة و التجريبية وتم اختبار القوة الانفجارية و التسديد والارتقاء وقمنا بإعداد مجموعة من التمرينات البليومترية الخاصة بكرة القدم لتطوير القوة الانفجارية والارتقاء و التسديد بعد تطبيق البرنامج قمنا بإجراء الاختبارات البعدية وتم التوصل الى: إن التدريب البليومتري كان له أثر في تنمية القوة الانفجارية لدى لاعبي كرة القدم (U19). إن التدريب البليومتري كان له أثر في تطوير صفة الارتقاء لدى لاعبي كرة القدم (U19). إن التدريب البليومتري كان له أثر في تطوير صفة التسديد لأبعد مسافة لدى لاعبي كرة القدم (U19). في ضوء الاستنتاجات التي توصلت اليها الدراسة خرج الباحث بمجموعة من الاقتراحات: التأكيد على استخدام التدريب البليومتري لتطوير القدرات البدنية. التأكيد على الاهتمام بوضع برامج بليومترية خلال الخطة السنوية للمدربين. الاهتمام من قبل العاملين في مجال كرة القدم بوضع مناهج تدريبية للبليومتري وتوزيعها بشكل مدروس للاستفادة منها. .............................................................Résumé............................................................................ L'étude visait à examiner l'impact d'un programme d'entraînement pliométrique sur le développement de la force explosive, du tir et du saut chez les joueurs de football U19, en utilisant des exercices pliométriques pour améliorer certaines capacités physiques. Nous avons utilisé une approche expérimentale qui était la plus appropriée pour cette étude. Pour cela, l'échantillon était composé de 22 joueurs du club de l'Union Sportive de Sedrata, qui évolue au niveau régional de première division à Annaba. L'échantillon était intentionnel et nous avons effectué des tests préliminaires pour les deux groupes, le groupe témoin et le groupe expérimental. Nous avons évalué la force explosive, le tir et le saut, puis nous avons conçu un ensemble d'exercices pliométriques spécifiques au football pour développer la force explosive, le saut et le tir. Après avoir appliqué le programme, nous avons effectué des tests postérieurs et nous avons obtenu les résultats suivants : L'entraînement pliométrique a eu un effet sur le développement de la force explosive chez les joueurs de football U19. L'entraînement pliométrique a eu un effet sur l'amélioration de la capacité de saut chez les joueurs de football U19. L'entraînement pliométrique a eu un effet sur l'amélioration de la capacité de tir à distance chez les joueurs de football U19. À la lumière des conclusions de l'étude, le chercheur propose les suggestions suivantes : Mettre l'accent sur l'utilisation de l'entraînement pliométrique pour développer les capacités physiques. Veiller à intégrer des programmes pliométriques dans le plan annuel des entraîneurs. Encourager les acteurs du football à élaborer des programmes d'entraînement pliométrique et à les distribuer de manière réfléchie pour en tirer profit.